Relapsing–remitting psychosis with malignant catatonia: a multidisciplinary challenge. Issue 1 (2nd January 2022) - Gerra, Maria Lidia; Mutti, Carlotta; Luviè, Lorenzo; Daniel, Benyamin Daniel; Florindo, Irene; Picetti, Edoardo; Parrino, Liborio; Marchesi, Carlo; Zinno, Lucia
ABSTRACT: Malignant catatonia is a life-threatening syndrome that could be observed in various psychiatric and neurological conditions. We describe the challenging case of a young woman with relapsing–remitting malignant catatonia, which finally resolve after electroconvulsive therapy (ECT). Details regarding her psychiatric symptoms, dynamics, and EEG features during each acute and post-acute phases of the disease are described and long-term follow-ups are provided. We emphasize the importance of a multidisciplinary cross talk between neurologists and psychiatrists to ensure adequate management of this dangerous condition. Knowledge and gaps in the field of autoimmune psychosis are also discussed.